Cities in Transition : world bank urban and local government strategy. - The World Bank (Washington, World Bank, 2000)
This report incorporates the World Bank's new strategy for an urbanizing world. It recognizes that cities and towns form the frontline in a global campaign to address issues of poverty and development opportunity. Guided by a vision of sustainable cities that are livable, competitive, well-governed and -managed, and bankable, this study argues that the Bank needs to view the city holistically while intervening selectively, facilitate city-led development process as well as support sound national urban policy frameworks; invest widely in urban knowledge generation, dissemination, and capacity building; and work through strengthened public and private partnerships at local, national, and international levels.
Include Bibliography Reference and Index Material.
Keywords: 71.14 urban society; World Bank Developing countries; City planning Developing countries Finance